2017
DOI: 10.1039/c6ta09423f
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition mechanisms in metal borohydrides and their ammoniates

Abstract: Ammoniation in metal borohydrides (MBs) with the form M (BH 4 ) x has been shown to lower their decomposition temperatures with M of low electronegativity (χ p 1.6), but raise it for high-χ p MBs (χ p 1.6). Although this behavior is just as desired, an understanding of the mechanisms that cause it is still lacking. Using ab initio methods, we elucidate those mechanisms and find that ammoniation always causes thermodynamic destabilization, explaining the observed lower decomposition temperatures for low-χ p MBs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Thus, the Zn cation assists the formation of with NH 3 . E b represents the calculated energy barrier.A previous study suggests that B 2 H 7 would combine with NH 3 to form NH 3 BH 3 and BH 4 in gas phase 37. It would be interesting to examine whether or not this process can occur…”
mentioning
confidence: 95%
“…Thus, the Zn cation assists the formation of with NH 3 . E b represents the calculated energy barrier.A previous study suggests that B 2 H 7 would combine with NH 3 to form NH 3 BH 3 and BH 4 in gas phase 37. It would be interesting to examine whether or not this process can occur…”
mentioning
confidence: 95%
“…In contrast, NH3 is strongly coordinated with high electronegativity metal cations (>1.6), resulting in direct H2 release in these materials. [27] Although this study has provided valuable insight of the decomposition processes of single metal cation AMBs, the results may not directly apply to double cations AMBs. For instance, the incorporation of LiBH4 (with low electronegativity of 0.98 for Li cation) into…”
Section: Introductionmentioning
confidence: 99%
“…[16,[23][24][25] The electronic structure and decomposition mechanisms of single metal cation AMBs have been studied by Density functional theory (DFT) calculation. [21,[25][26][27] Recent theoretic study indicates that the ammonia is weakly bound to the metal cations with low electronegativity (<1. 2) in AMBs, therefore tend to release ammonia at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the ammine-stabilized metal borohydrides can be formed by ball milling of the ammine metal chloride and LiBH 4 , as shown for M(BH 4 ) 3 •5NH 3 (M = Ti 3+ , V 3+ ) and Ti(BH 4 ) 3 •3NH 3 [35,36]. Theoretical calculations have revealed that the metal borohydrides are always thermodynamically destabilized by ammonia, but in the case of the unstable metal borohydrides with a high Pauling electronegativity of the metal (χ P ≥ 1.6), the compounds are kinetically stabilized, as ammonia protects the metal from reduction and thereby alters the decomposition pathway and suppresses the release of B 2 H 6 [37].…”
Section: Introductionmentioning
confidence: 99%